A comparative study of the effects of electoral institutions on campaigns - Sudulich, Laura; Trumm, Siim (Cambridge University Press, 2017)
A long tradition of studies in political science has unveiled the effects of electoral institutions on party systems and parliamentary representation. Yet, their effects on campaign activities remain overlooked. Research in this tradition still lacks a strong comparative element able to explore the nuanced role that electoral institutions play in shaping individual-level campaigns during first-order parliamentary elections. We use data from a variety of national candidate studies to address this lacuna, showing that the electoral mobilisation efforts put in place by candidates are affected by the structure of the electoral institutions. Candidate-centred electoral systems propel higher mobilisation efforts, in terms of both campaign intensity and complexity. Moreover, we find that candidate-centred electoral systems shift the campaign focus towards individuals more than parties. By directly addressing the effects of electoral institutions on campaign behaviour, our study contributes to the wider debate on their role in promoting political engagement and mobilisation. The implications of our results concern the effects of electoral institutions on political competition, indicating that the extent to which electoral institutions impact upon it go well beyond what has been shown to date.